PRINSIP SYURA’ DALAM KONSTITUSIONAL ISLAM - Lukman Santoso (AS-SALAM, 2012)
This topic examines concept ?syura? (conference; negoisation) and how to implement ?syura? to the context of constitutional state right now. Including the offending with rechstaat/ rule of law. Syura is defined as the main principle for solving the social, politic, and government problems. Syura is the way to give the opprtunity to the society who has an ablity to participate for making a decision which binds as well as in the law regulation and politic policy. But the implementation of syura althought the institutionalization of syura, no nash of Al-Qur?an that decribes about it. Prophed Muhammad SAW?that instituted and cultured syura?did not leave the specific pattern and the form. Beause of that,  the moslems right now and to te next, the partern and the form of  that implementation, are free to initiative. So it can be appropriated with the condition and the reality. Including that relevance with the parliamentary democratie concept or the exixtence of legislative instiution, especially Indonesia.